Influence of the fertilization on the winter wheat in the crop rotations and in the long-term monoculture - M. Babulicová (Plant, Soil and Environment, 2008)
The effect of mineral and organic fertilization on grain yield and quality of winter wheat in crop rotations and in continuous cropping was investigated. The study was conducted in Borovce (near Piešťany) on Luvi-Haplic Chernozem in the years 2002-2004. Mineral and organic fertilization of winter wheat growing in monoculture was more effective than mineral fertilization in crop rotations. In the case of winter wheat growing in monoculture, statistically higher grain yield (5.10 t/ha) was obtained in the variant with straw and green manure incorporation compared to the control variant (4.73 t/ha) and the variant with straw incorporation (4.75 t/ha). In the Solara variety, statistically higher number of plants before harvest was recorded in the variant with straw and green manure incorporation (194 plants per 1 m2) than in the variant with straw incorporation only (149 plants per 1 m2). As for the winter wheat grain in the sequence 2, based on the wet gluten content (30.3%) the Solara variety was classified in the elite class E in the variant with straw and green manure incorporation, and in the improving class A in the control variant.